FORMATION OF COGNITIVE GYMNASIUM STUDENTS INTEREST OF HUMANISTIC DIRECTION (Pedagogy of Higher and Secondary Education, 2006)
The peculiarities of coqnitive of humane trend and ways of their forming is nevealed in the article.